The effect of balneotherapy with natural mineral dissolved water on dry skin in atopic dermatitis: A phase IIa, nonrandomized, controlled study - Akihiko Uchiyama; Chisako Fujiwara; Yuta Inoue; Kazushi Uchida; Miyabi Hiyama; Hideyuki Itabashi; Sei‐ichiro Motegi (Frontiers Media S.A., 2021)
Abstract Objectives It has been known that the use of moisturizers is useful in preventing the onset and maintaining remission of atopic dermatitis (AD). We recently focused on the moisturizing effect of natural mineral dissolved water and have conducted various studies. In this study, we investigated whether the bath treatment using natural mineral dissolved water can improve dry skin in AD patient in prospective nonblind, nonrandomized controlled study. Methods Thirteen adults with almost clear to moderate AD took bath therapy using tap water for 13 days, followed by bath therapy using natural mineral dissolved water for 13 days. Changes in the severity scoring, patient‐oriented eczema measure, pruritus numerical rating scale, transepidermal water loss (TEWL) and hydration were evaluated at day1, 14 and 28. Results Tap water using bath treatment did not change the severity scoring and itch associated score, and it partially decrease TEWL when compared with baseline condition. Bath treatment using natural mineral dissolved water slightly decrease eczema area and severity index (EASI) score and significantly decrease TEWL with respect to baseline condition. Moreover, in relatively severe AD analysis, bath treatment with mineral dissolved water significantly decreased EASI and TEWL. Conclusions Based on these results, bathing with natural mineral dissolved water may be effective in improving the dry skin of atopic dermatitis. Further studies are needed to evaluate its effects more clearly.